Beginning musical theatre dance - Harris, Diana Dart (Interactive dance series, 2016)
Beginning Musical Theatre Dance introduces students to basic musical theatre dance techniques from a variety of genres, forms, and styles and explains how to put them into practice for performance on stage. Part of Human Kinetics' Interactive Dance Series, the text and web resource offer students what they need to know about auditions, rehearsals, performing, and caring for themselves so they can have a successful experience in a musical theatre dance course. Designed for students enrolled in introductory musical theatre dance courses, the text contains photos and descriptions of basic warm-up exercises, center work, steps from a variety of dance genres used in musical theatre dance, partnering, and lifts. For those new to dance, the text provides an orientation to the structure of a musical theatre dance class and includes information on meeting class expectations, dressing appropriately, preparing mentally and physically, maintaining proper nutrition and hydration, and avoiding injury.
Keywords: Dance : Study and teaching; Musicals; Musical theater; tanssi; musiikkiteatteri (taiteet); musikaalit; dans; musikteater (teaterkonst); musikaler